Eco-friendly management of tomato wilt disease caused by Fusarium sp. in Sindh Province, Pakistan - Gul Poussio; Manzoor Abro; Rehana Syed; Muhammad Khaskheli; Jamal Hajano (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The investigation of the different plant waste parts for ecofriendly management of Fusarium sp. was carried out.Method The disease associated fungus was isolated from the diseased specimen and purified. The twelve different aqueous plant extracts were prepared and evaluated against test pathogen in laboratory, pots and in filed conditions.Results Among the tested aqueous plant extracts the neem seed, thorn apple, garlic, neem leaves and eucalyptus were found the most effective providing highest growth inhibition percent of test fungus. The lowest plant mortality and disease incidence percent, maximum plant biomass and minimum root infection percent were observed in plans treated with neem leaves, neem seed, garlic, thorn apple and eucalyptus extracts in pot experiment. In field experiment, the extracts of neem leaves, thorn apple and neem seed produced the lowest disease incidence and mortality percentage as compared to other extracts. The extract of garlic was noted as moderate effective among the treatments. The eucalyptus extract was found as less effective. The maximum height and weight of individual plant was observed in the treatment of neem leaves than in neem seed, garlic, eucalyptus, and thorn apple extracts. Significantly, the highest fruit yield was recorded in plant treated with neem leaves extracts followed by neem seed, garlic, eucalyptus, and thorn apple.Conclusion The study showed that neem leaves, neem seed and garlic, eucalyptus and thorn apple extracts are potential aqueous extracts for ecofriendly management of tomato fusarium wilt disease.